The Measure of Public and Private Law (on Material of Ukrainian Legislation) - Stovba, Oleksiy (Teisė, 2022)
The article is about the phenomenon of guilt as measure of the public and private law. The guilt originally expresses itself as based on the causality. The legal science considers the guilt as the psychological attitude of the human Being, who has committed the offence towards its social consequences. The guilt as causal relation is localized between intent or negligent deed and caused damage. The form of guilt (intent or negligence) is a marker which allows us to distinguish the areas of private law and public law. The gross negligence is “gray area” between public and private law. So, the true ground of the civil responsibility is guilt as causa, and the determination of guilt as psychical attitude to the deed and its consequences is valid to the area of public law only.
Keywords: guilt; psychological attitude; causa; intent; negligence; damage